Effect of dermatological consultation on survival in patients with checkpoint inhibitor‐associated cutaneous toxicity. (17th May 2021) - Thompson, L.L.; Li, E.B.; Krasnow, N.A.; Chang, M.S.; Said, J.T.; Molina, G.E.; Polyakov, N.J.; Yoon, J.; Dee, E.C.; Huang, K.; Blum, A.E.; Kuchroo, J.R.; et al.
Summary: Background: Cutaneous immune‐related adverse events (cirAEs) are a common side‐effect of immune checkpoint inhibitors (ICIs). However, prior work examining these toxicities in detail has considered only the fraction of events evaluated by dermatologists. Associations between dermatology referral, cirAE treatment and survival outcomes remain underexplored across care settings. Objectives: To comprehensively categorize cirAE patterns among all patients treated with immunotherapy at our institution, and to evaluate: (i) the effect of dermatology referral on cirAE treatment and (ii) the impact of cirAE treatment on survival. Methods: This was a retrospective cohort analysis of patients with cancer who initiated ICI therapy between 1 January 2016 and 8 March 2019 and developed one or more cirAEs, as screened for using International Classification of Diseases 10th revision codes and confirmed via manual chart review ( n = 358). All relevant information documented prior to 31 March 2020 was included. Results: CirAEs evaluated by dermatologists were significantly more likely to be treated than cirAEs that were not referred (odds ratio 6·08, P < 0·001). Patients who received any cirAE treatment had improved progression‐free survival [hazard ratio (HR) 0·59, P = 0·001] and overall survival (HR 0·58, P = 0·007) compared with those who did not. Conclusions: CirAEs evaluated by dermatologists were significantly more likely to be treated than cirAEs that were not referred, and patients who received any treatment for a cirAE had improved survival outcomes. Abstract : What is already known about this topic? Cutaneous immune‐related adverse events (cirAEs) are common among patients on immune checkpoint inhibitor (ICI) therapy, occurring in up to one‐third of ICI monotherapy recipients. Despite the prevalence of cirAEs, the relationships between dermatology referral, cirAE treatment and survival outcomes remain underexplored. What does this study add? CirAEs evaluated by dermatologists were significantly more likely to be treated than cirAEs that were not referred, and patients who received treatment had improved survival. Our findings underscore the vital role of dermatologists in oncological care and suggest that closer collaboration between oncologists and dermatologists may be valuable in supporting comprehensive cirAE treatment. Additionally, our findings suggest that cirAE treatment may serve as a potentially important marker for survival in patients with cancer. Linked Comment: S. Walsh. Br J Dermatol 2021; 185:486 .